Circumventing cigarette regulation: Product characteristics of cigarette-like cigarillos on the Dutch market - Jeroen L. A. Pennings; Charlotte G. G. M. Pauwels; Erna Schenk; Reinskje Talhout (Tobacco Induced Diseases)
Introduction Cigarillos have been reported to provide an alternative to cigarettes with a characterizing flavor, which are banned in the European Union. Additionally, they are cheaper than cigarettes. To better inform policy making, we wanted to gain better insight into the market situation for cigarillos in the Netherlands.